Increased inflammatory response of blood cells to repeated bout of endurance exercise - Degerstrom, J.; Osterud, B. (Medicine & Science in Sports & Exercise, 2006)
Purpose: The aim of the present study was to assess the effects of two 30-min consecutive exercise bouts on a treadmill at 80% VO2 separated by a 4-h rest interval, on blood cell counts and the production of tissue factor, cytokines, and eicosanoids in lipopolysaccharide (LPS)-stimulated blood.